How can we Make you Stay? Identifying Motivating Factors to Volunteer Retention in Non-Profit Organizations - Cobos, Liza; Templeton, Amanda (Journal of Tourism Management Research, 2022)
Many non-profit organizations depend on volunteers to provide services to their clients thus helping to alleviate some of the costs and financial burdens non-profits face. A volunteer’s motivation and satisfaction drivers are varied thus making the task of attracting and retaining volunteers a difficult one. Since volunteers are a vital part of any non-profit and volunteer supported organization, retention initiatives are crucial to the organization’s success. The aim of this study is to examine the impact of organizational support, group integration, empowerment and participation efficacy on volunteer satisfaction and retention. Over 100 volunteers, from a Central Florida organization, were surveyed to: 1) measure their motivating factors and satisfaction with various aspects of their volunteer experience and 2) measure their intentions to remain as a volunteer. The results of the hierarchical multiple regression suggest that participation efficacy and organizational support are significant predictors to intent to remain with the organization.